(untitled) (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
The development of communicative competence is one of the primary objectives of modern English Language Teaching (ELT). As language education has shifted from traditional grammar-focused instruction to communicative approaches, educators have increasingly sought classroom practices that promote meaningful interaction and authentic language use. Debate and discussion activities have emerged as effective pedagogical tools for fostering speaking proficiency, critical thinking, collaboration, and learner autonomy. This article examines the theoretical foundations of debate and discussion activities, explores their benefits in language learning, and provides practical recommendations for their implementation in English language classrooms.